Effectiveness of systematic didactic workshops in improving university students’ communicative competencies - Teófilo F. Valentín Melgarejo; Daniel J. Pariona Cervantes; Isabel A. Delzo Calderón; Nora E. Hinostroza Campos; Dionicio L. Basilio; Pablo L. Valentín Melgarejo; Víctor L. Albornoz Dávila; Raúl M. Lovatón; Pablo L. La Madrid Vivar; Josué C. Leandro; Shuffer G. Rojas; Flaviano A. Zenteno Ruiz (Institute of Advanced Engineering and Science, 2026)
The study examined the effectiveness of structured didactic methods in improving communicative competence among 26 undergraduate university students using a pretest–posttest experimental design. The intervention consisted of guided oral presentations, structured debates, dialogic interaction, guided writing with drafting–revision cycles, and scaffolded reading activities based on inferential and critical questioning. These techniques were implemented through a sequence of instructional workshops organized into baseline assessment, didactic intervention, and post-intervention evaluation phases. Data was analyzed using descriptive and inferential statistics, including paired-sample t-tests, effect size estimation (Cohen’s d), normalized gain (Hake’s g), and 95% confidence intervals (CI) to determine the magnitude and reliability of learning outcomes. The results revealed substantial improvements across all communicative domains after the intervention. At baseline, performance was low to moderate across competencies. In particular, 0.0% in writing indicates that no student met the predefined proficiency threshold at pretest, while reading comprehension showed 11.5% proficiency, and oral expression 19.2%. The performance increased markedly followed by intervention, with posttest scores were 80.8% in oral expression, 69.3% in writing, and 73.1% in reading. Such gains were statistically significant (p<0.001) and had high effect sizes (Cohen’s d=2.17 to 2.31). Normalized gain scores (g=0.56-0.62) reflected medium-to high-level instructional effectiveness on all competencies. The overlap of statistical results, effect sizes, and learning patterns prove that the intervention is pedagogically effective, and it is relevant to be used in the context of higher education to reinforce the oral, written, and reading abilities with the help of evidence-based teaching methods.